Integrating ESG Metrics into Financial Reporting: Aligning Profit with Purpose in the Indonesian Corporate Sector - Riana, Nia (KRIEZ ACADEMY : Journal of development and community service, 2024)
Environmental, Social, and Governance (ESG) factors have emerged as a cornerstone for assessing corporate sustainability and long-term value creation. This paper delves into the critical process of integrating ESG metrics into the financial reporting ecosystem of Indonesia. It addresses the growing demand from investors, regulators, and a conscious public for corporate transparency beyond traditional financial statements. The study synthesizes a comparative analysis of leading global ESG frameworks, including the Global Reporting Initiative (GRI), Sustainability Accounting Standards Board (SASB), and the Task Force on Climate-related Financial Disclosures (TCFD). Through a mixed-methods research design, which includes a comprehensive content review of 30 Indonesian listed companies' annual reports and interviews with industry experts, the paper identifies significant gaps and inconsistencies in current reporting practices. It analyzes the specific regulatory, operational, and strategic implications for Indonesian firms across various sectors. Based on these findings, the paper proposes a strategic roadmap for embedding ESG indicators into mainstream accounting and disclosure practices, advocating for a localized, harmonized framework. The ultimate aim is to demonstrate that by aligning corporate purpose with robust ESG performance, Indonesian companies can not only mitigate risks and meet stakeholder expectations but also unlock new avenues for sustainable value and long-term competitive advantage.